Exploring the genetic causal relationship between physical activity and migraine in European population based on Mendelian randomization analysis - Wang, Jinfu; Yang, Guan (Frontiers in Neurology, 2024)
Previous studies have shown a connection between physical activity and migraines, but they don't prove a cause-andeffect relationship due to potential biases in observational methods. Utilizing accelerometer-measured physical activity data from a cohort of 377,234 participants in the UK Biobank and information from 599,356 European migraine patients (including 48,975 cases and 550,381 controls) obtained from 24 cohorts, we performed a bidirectional Mendelian randomization analysis to investigate the genetic bidirectional causal relationship between accelerometer-measured physical activity and migraines. Research findings indicated a slight negative genetic correlation between "average acceleration" physical activity (rg = -0.091, p = 0.011), overall physical activity (rg = -0.081, p = 0.017), and migraine. Nevertheless, no shared genetic components were observed between migraine and "fraction of accelerations > 425 mg" of physical activity (rg = -0.124, p = 0.076). The study results also demonstrated a lack of genetic bidirectional causality between accelerometer-measured physical activity and migraine ("average acceleration", OR = 1.002, 95% CI 0.975-1.031, p = 0.855, "fraction of accelerations > 425 mg", OR = 1.127, 95% CI 0.802-1.583, p = 0.488, overall physical activity, OR = 0.961, 95% CI 0.713-1.296, p = 0.799), and vice versa.Additionally, this lack of causal association persists even after adjusting for obesity (OR =1.005, p = 0.578), education (OR =1.019, p = 0.143), and depression (OR =1.005, p = 0.847), either separately or simultaneously. The Mendelian randomization results based on genetic data do not provide support for a causal association between physical activity and migraine.